Eosinophilic Granulomatous Dermatitis Due to Hairy vetch (Vicia villosa Roth) Poisoning in a Holstein Cow - Eroksuz, Y.; Polat, E.; Incili, C. Akdeniz; Karabulut, B.; Sagliyan, A.; Eroksuz, H. (Hellenic Veterinary Medical Soc, 2023)
Eosinophilic granulomatous dermatitis has been reported due to hairy vetch (Vicia villosa Roth) con-sumption in a 3-year-old Holstein cow. The cow had dermatitis over the face, neck, palpebral skin and perineum in the last 2-months. The other 3 animals also exhibited similar skin lesions on the same farm.Histological examination of biopsy samples indicated the presence of multifocal eosinophilic granulomatous derma-titis. Immunohistochemical analysis showed that T lymphocytes were the predominant inflammatory cells in granu-lomatous lesions, whereas B cells and macrophages were less prominent. After the owner stopped feeding cows with the vetch, the skin lesions regressed 6 months later and completely resolved alter 12 months. The final diagnosis was hairy vetch poisoning based on plant-lesion relationship, presence of the plant material and character and distribution of the skin lesions and the healing of the lesions after removing the plant from the ration. It is uncommon, but not a rare disease in cattle,however, up to date only one suspected case of hairy vetch poisoning was reported in Turkey.In conclusion, this report demonstrates that vetch poisoning in cattle could be diagnosed by skin lesions which might also regress by removing vetch from the diet.
Keywords: Bovine; granulomatous dermatitis; hairy vetch (Vicia villosa Roth); pathological changes